Simulation and Evaluation of a Variable Effective Focal Length of Refractive Binocular Telescope - K. Shwayyea, Alaa; Hasan, Alaa Badr (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The telescope works to magnify images of distant objects in general, but it needs special optical elements to complete the task to the fullest. The telescope needs optimal balance values of the optical parameters used to produce the best image, such as the effective focal length and the diameter of the pupil aperture, which are combined in a single concept called the focal number. The ground-based binary telescope relies on special lenses and an exceptional prism to achieve a hybrid design that produces clear images of relatively distant terrestrial objects. The pupil diameter of the telescope is relatively large to ensure that the largest possible amount of light is received, and as a result, a good image is obtained.In this work, an achromatic objective lens and a Porro prism has been used to reduce the length of the telescope and change the path of the rays to the eyepiece, in addition to the presence of a flat convex lens behind the prism to collect the rays coming from it to reach the eyepiece. The effective focal length of the optical system was changed to illustrate the effect of this factor on the performance of a telescope and as a result of its effect on the image quality.